ne-dimensional Anderson model with dichotomic correlation - Kaya, T. (SPRINGER, 2007)
A one-dimensional diagonal tight binding electronic system with dichotomic correlated disorder is investigated. The correlation of random potential exponentially decays with distance and also with the dichotomic correlation parameter lambda. Using a appropriate approximation, an analytical transmission coefficient expression is obtained. The obtained analytical expression is then tested against the result of the direct numerical computation of the average transmission coefficient for the Anderson model, by changing the system parameters. In the thermodynamic limit the transmission coefficient relation indicates the absence of localization-delocalization transition, which is entirely consistent with numerical predictions.
Keywords: LOCALIZATION-DELOCALIZATION TRANSITION; SCALING THEORY; ABSENCE; DIFFUSION; TRANSPORT; EXPONENT; CHAINS; Physics